Angles on Aran: constructing connection in the work of J.M. Synge, Robert Flaherty and Sean Scully. Issue 4 (21st April 2019) - Arrowsmith, Aidan
ABSTRACT: This article focuses on three Irish diasporic representations of the Aran Islands, and is innovative in analysing all three in the light of recent cultural theory, especially around postmemory and postmodernity. In particular, the paintings and photographs of Irish-British artist Sean Scully, especially Walls of Aran (2007), are given a first appraisal in this light. Further angles on Aran, and contexts for Scully's work, are provided by Man of Aran by Irish-American filmmaker Robert Flaherty (1934), and the photographic and literary representations of Aran produced by Anglo-Irish Ascendancy writer J.M. Synge between 1898 and 1902. The works are analysed in relation to a tradition of colonialist and nationalist primitivism and the essay builds a picture of diasporic romanticism that spans three quite different historical moments.